Conceptualizing precarious employment through the lens of social reproduction: Potential implications for health research and action - Emilia F. Vignola; Emily Q. Ahonen; Luis Saavedra; Emma K. Tsui (SSM: Qualitative Research in Health)
Research on the health and well-being impact of precarious employment (PE) commonly conceptualizes employment as a relation of power between workers and employers, a perspective informed by power relations and relational social class theories. Social reproduction theory is a less common but complementary conceptual lens that can be used to investigate PE and health, in which the nature of work has relevance for the quality of employment. Social reproduction theory points to relations between groups of workers who are valued differently based on the capacity of their work to generate profit. Attending to relations between workers based on value, in addition to the well-established power relation between workers and employers, may point to consequences for health and well-being that are worth exploring empirically, and could serve as another tool to spur collective action around PE and its health effects. We provide an illustration and discuss the potential implications of this theoretical approach using data from in-depth interviews conducted in 2022 among precariously employed food workers in New York City.